Hippo signaling pathway in cervical cancer: insights into mechanisms and therapeutic potential - Sun, Yanmei; Zhou, Fei; Zhong, Xiuhong; Lv, Xiatong; Liu, Yue; Zhang, Yi; Fine, Ryan D.; Li, Mingguang (Frontiers in Oncology, 2025)
Cervical cancer (CC) remains a major global health threat to women, with persistent infection by high-risk human papillomavirus (HPV) being the primary etiological factor. In recent years, the Hippo signaling pathway has emerged as a critical regulator of CC pathogenesis and a promising therapeutic target. Aberrant activation of its key effectors, Yes-associated protein (YAP, also referred to as YAP1) and transcriptional coactivator with PDZ-binding motif (TAZ), is closely linked to enhanced proliferation, migration, and invasion of CC cells. This review provides a comprehensive analysis of the intricate crosstalk between the Hippo pathway and HPV-driven oncogenesis. We detail specific mechanisms, such as how HPV oncoproteins (e.g., E6/E7) directly stabilize YAP/TAZ and disrupt the tumor-suppressive YAP1-LATS2 feedback loop, thereby synergistically promoting carcinogenesis. Furthermore, we explore the regulatory network involving non-coding RNAs (ncRNAs), including how miRNAs and lncRNAs modulate Hippo components to influence CC progression. Beyond mechanistic insights, this review critically evaluates the therapeutic potential of targeting the Hippo pathway, discussing innovative strategies such as small-molecule inhibitors, rational combinations with immunotherapy or chemo/radiotherapy, and the pathway’s significant role in mediating drug resistance. Ultimately, this work aims to consolidate a theoretical foundation for developing novel, mechanism-based treatment strategies for CC, offering new perspectives and actionable targets for future clinical intervention.